2014
DOI: 10.1158/0008-5472.can-13-3470
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-Mediated Autophagy Dependence Identifies Subtypes of Breast Cancer Where Autophagy Inhibition Can Be Efficacious

Abstract: Autophagy is a protein and organelle degradation pathway that is involved in diverse diseases including cancer. Recent evidence suggests that autophagy is a cell survival mechanism in tumor cells and that its inhibition especially in combination with other therapy could be beneficial but it remains unclear if all cancer cells behave the same way when autophagy is inhibited. We inhibited autophagy in a panel of breast cancer cell lines and found that some of them are dependent on autophagy for survival even in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
151
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(164 citation statements)
references
References 47 publications
13
151
0
Order By: Relevance
“…Second, human cancer cell lines can be unaffected by autophagy suppression (e.g., Maycotte et al 2014;Mandelbaum et al 2015). Human cancer cell lines often tolerate genome-editing approaches that delete Atg genes when grown in two-dimensional (2D) culture with replete culture medium , which is in contrast to the findings from spontaneously arising tumors.…”
Section: Arguments Against Targeting the Autophagy Pathway In Cancermentioning
confidence: 99%
“…Second, human cancer cell lines can be unaffected by autophagy suppression (e.g., Maycotte et al 2014;Mandelbaum et al 2015). Human cancer cell lines often tolerate genome-editing approaches that delete Atg genes when grown in two-dimensional (2D) culture with replete culture medium , which is in contrast to the findings from spontaneously arising tumors.…”
Section: Arguments Against Targeting the Autophagy Pathway In Cancermentioning
confidence: 99%
“…However, in established tumor cells, which are constantly exposed to mutations, radiation, chemotherapy or targeted agents, autophagy may act as an additional means for survival. 3 Although the exact role of autophagy is debatable in different tumor models or in different pathological conditions, certain tumors are proposed to be 'autophagy addicted,' 4 and numerous crosstalk occurs between autophagy and other cancer-promoting pathways. 5 STAT3 (signal transducer and activator of transcription 3 [acute-phase response factor]) is a latent transcription factor that mediates extracellular signals such as cytokines and growth factors through interaction with polypeptide receptors at the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…We were interested to test if autophagy inhibition, which is being tested in the clinic as a chemosensitization strategy as a means to improve cancer therapy, could affect the behavior of drug-resistant cells. Because cancer cells can show both growth inhibitory and stimulatory effects to autophagy inhibition (Guo et al, 2011;Maycotte et al, 2014), treatment with pharmacological autophagy inhibitors that would affect both drug sensitive and resistant cells equally is unable to test rigorously for non-cellautonomous effects of autophagy in a heterogeneous tumor cell population. We previously reported that autophagy inhibition sensitizes cancer cells to TRAIL-induced apoptosis by making it easier for the cancer cells to activate caspases after mitochondrial membrane disruption (Thorburn et al, 2014b).…”
Section: Resultsmentioning
confidence: 99%